River Meanders and Their Impact on Real Estate Ownership Case Study (Al-Shirqat District) - Sami Abdullah, Yasir; Kamel AL-Rawi, Moheb (Journal of Planner and Development, 2024)
Changing river courses is a long-standing problem; this is especially true for cities located along these routes. This causes erosion and sedimentation of river banks, which negatively affects the properties located there. The aim of this study was to determine the negative impacts of river course changes on property ownership using modern software that records these changes to reach planning solutions. The survey area included the Al-Shirqat region in the Salahuddin governorate of Iraq. An analytical method was used to compare old satellite images from 1968 with current images from 2022. This comparison revealed changes in river flow, calculated levels of erosion, which were then compared with cadastral maps to assess property damage. GIS software and other relevant tools were used for this. Water flows cause continuous damage and siltation of river banks; this is affected by the speed of the water flow and the type of land. These changes have a negative impact on property ownership and the affected areas. Therefore, measures need to be taken to reduce river bank erosion and appropriately distribute services to areas near the river banks to mitigate the negative effects of these changes.